SHAXSDA SALBIY TUZILMALARNING PAYDO BO‘LISHI - Shomurotov Ulugbek Melikboboyevich, Madaminov Doniyorbek Davrbek o‘g‘li, Xudoyqulov Azamat Jo‘rakul o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides concepts related to the existing moral development of a person and the ability to get out of the conflicts that arise in this development. Information is given about lying about the satisfaction of their needs, striving for recognition among their peers.